Comparison of laser speckle contrast imaging with laser Doppler perfusion imaging for tissue perfusion measurement. (29th December 2022) - Guven, Goksel; Dijkstra, Annemieke; Kuijper, Tjallingius Martijn; Trommel, Nicole; van Baar, Margriet Elisabeth; Topeli, Arzu; Ince, Can; van der Vlies, Cornelis Hendrik
Abstract: Objective: Laser‐based tissue perfusion monitoring techniques have been increasingly used in animal and human research to assess blood flow. However, these techniques use arbitrary units, and knowledge about their comparability is scarce. This study aimed to model the relationship between laser speckle contrast imaging (LSCI) and laser Doppler perfusion imaging (LDPI), for measuring tissue perfusion over a wide range of blood flux values. Methods: Fifteen healthy volunteers (53% female, median age 29 [IQR 22–40] years) were enrolled in this study. We performed iontophoresis with sodium nitroprusside on the forearm to induce regional vasodilation to increase skin blood flux. Besides, a stepwise vascular occlusion was applied on the contralateral upper arm to reduce blood flux. Both techniques were compared using a linear mixed model analysis. Results: Baseline blood flux values measured by LSCI were 33 ± 6.5 arbitrary unit (AU) (Coefficient of variation [CV] = 20%) and by LDPI 60 ± 11.5 AU (CV = 19%). At the end of the iontophoresis protocol, the regional blood flux increased to 724 ± 412% and 259 ± 87% of baseline measured by LDPI and LSCI, respectively. On the other hand, during the stepwise vascular occlusion test, the blood flux reduced to 212 ± 40% and 412 ± 177% of its baseline at LDPI and LSCI, respectively. A strong correlation was found between the LSCI and LDPI instruments at increased blood flux with respect to baseline skin blood flux; however, the correlation was weak at reduced blood flux with respect to baseline. Discussion: LSCI and LDPI instruments are highly linear for blood flux higher than baseline skin blood flux; however, the correlation decreased for blood flux lower than baseline. This study's findings could be a basis for using LSCI in specific patient populations, such as burn care.